Valley of Shining Stone : The Story of Abiquiu - Poling-Kempes, Lesley (Book collections on Project MUSE., 1997)
Reading almost like a novel, this book, says writer Marc Simmons, "gives the reader not only the history but the feel of this unusual place." Georgie O'Keeffe captured on canvas as the valley's cliffs, canyons, and turquoise sides, but her life and death here are only a small part of the centuries-long saga. Here, too, are Pueblo Indians, Utes, Navajos, Jicarilla Apaches, Hispanos, and Anglos - many lives tangled together, yet also separate and distinct. Indispensable for travelers, pure pleasure for history buffs and general readers, these pages are a magic carpet to a magic land: Abiquiu, Ghost Ranch, the Valley of Shining Stone.